Critiques in the margins: Contextualizing mughulṭāy b. qilīj’s (d. 762/1361) gloss on the sīra - YILDIZ, GÜLLÜ (My University, 2023)
This article examines Mughulṭāy b. Qilīj’s (d. 762/1361) al-Zahr al-bāsim fī siyar Abī al-Qāsim, a ḥāshiya (gloss, marginal notes) on ʿAbd al-Raḥmān al-Suhaylī’s (d. 581/1185) commentary on Ibn Isḥāq’s Sīra. Drawing on evidence from Mamlūk-era chronicles, biographical dictionaries, and commentarial introductions, it analyzes Mughulṭāy b. Qilīj as a historical figure and the context and content of his work. This is done in order to demonstrate how commentaries and glosses are deeply related to the scholarly and cultural life of the period. These resources testify to the antagonistic relationship between Mughulṭāy and his opponents and to the ensuing rivalry between them. Hence, this article seeks to examine the correlation between his personality and the rationale for his commentary, to determine the reasons behind his choice of text to write a gloss on and his sustained and harsh criticism against al-Suhaylī and his scholarly legacy.